PRACTICE REALITY OF THE EXTENSION MANAGERS FOR PARTICIPATORY LEADERSHIP IN THE AGRICULTURAL EXTENSION SYSTEM / IRAQ - AL- Salhi, Ahmed Thwaini Hdoom; Salman, Mithal Abdul Latif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research was aimed to identify the reality of extension managers’ practice of participatory leadership in the agricultural extension system from view of agricultural extension workers in Iraq, through a questionnaire include 22 items distribute over three. The research community include all 15 province of Iraq, A random sample is taken from the province of Iraq (53%) and (8) province, namely (Dhi Qar, Maysan, Holy Karbala, Al-Qadisiyah, Babylon, Anbar, Diyala, Kirkuk) and a proportional, stratified random sample of (51%) is taken from agricultural extension workers distribute among the agricultural directorates and training extension centers, the number is (307, 133) and (157, 68) respectively, The results of revealed that the reality of practicing participatory leadership among extension managers from view of agricultural extension workers is low level , with an overall arithmetic mean of (1.96) scores and a standard deviation of (1.01) scores. The average responses of the sample members to all areas are low level , and they are, in order, as follows: Respectively (2.04 for human relations, 1.97 for delegation of authority, 1.87 for participation in decision-making), the study recommended the necessity of involving the managers activing with them in making decisions to improve the reality of the extension works.